Oracle the education: bodies and writings in favor of a pedagogy of dispersions (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The text discusses the possibilities of an oracular way of thinking about formative processes, based on the relationships between bodies, movement, and writing, as experienced in an extension course developed since 2020. The notion of the oracle, in its poetic and creative forces, is debated and conceived as a way of producing and inhabiting creative processes that are fundamental to education, understood as a gesture in favor of the dispersion of meanings and the multiplication of opportunities for fabulation.
Keywords: oracular apparatus; body and writing; body and education; poetic; fabulation